Helminthiasis in Maasai ranches in Kenya - Ndarathi, C.M.; Waghela, S.; Semenye, P.P. (1989)
A survey was carried out to determine the level of gastrointestinal parasite infections in cattle, sheep and goats in three Maasai group ranches (Olkarkar, Merueshi and Mbirikani) in Kajiadio District of Kenya. Strongylosis was the most prevalent gastrointestinal infection. Between 60-70 percent of the sheep and goats were infected with gastrointestinal parasites, while 40 percent of the cattle were infected. The rate of infection correlated with age in cattle with most of the cases occuring in calves which also suffered heavier parasitison. Coccidiosis was second to strongylosis in prevalence, mainly in calves, kids and lambs. Infection with other parasites was less than 6 percent.